Bất ổn chính sách kinh tế toàn cầu và nắm giữ tiền mặt của doanh nghiệp niêm yết tại Việt Nam - Nguyễn Thu , Hiền (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2026)
This study examines the relationship between global economic policy uncertainty and corporate cash holdings in Vietnam. Using a sample of 661 companies listed on the Ho Chi Minh Stock Exchange and the Hanoi Stock Exchange during the period 2005–2023, the author finds evidence that increases in global economic policy uncertainty are associated with a decline in cash holdings among Vietnamese firms. These results support both the precautionary motive hypothesis, whereby firms reduce precautionary cash demand in anticipation of lower investment, and the cash flow sensitivity hypothesis under conditions of capital constraints. The author further identifies the main channels through which global economic policy uncertainty affects corporate cash holdings in Vietnam, including: (i) a reduction in operating cash flow; (ii) reductions in current and future investment, and (iii) a decrease in financial leverage and an increase in payouts. These effects are more pronounced among high-growth firms and financially constrained firms. Moreover, the adverse impact of reduced cash holdings on firms’ innovation orientation and risk-taking behavior is particularly evident in firms with higher risk tolerance, leading to important managerial and policy implications for both corporate decision-makers and government authorities.